2011
DOI: 10.1108/02683941111139010
|View full text |Cite
|
Sign up to set email alerts
|

Sex and position status differences in workplace aggression

Abstract: PurposeThis study aims to examine sex and position status differences in the experience of workplace aggression. Based on the imbalance of power thesis, the aim is to posit that: women would report targeting other women; men would report targeting either sex; supervisors would report targeting a peer or subordinate; victims would report that a supervisor more often uses indirect forms of aggression; a peer more often uses direct forms of aggression; and; after controlling for position status, men would report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…It is interesting to notice that in our study men and managers reported better mental health that women and employees in lower job positions. This finding is congruent with previous literature that has shown that: (a) women reported more negative health effects, such as post-traumatic symptoms, as a result of exposure to bullying behaviors (e.g., Rodríguez-Muñoz et al 2010 ); perpetrators of bullying are likely to be men and employees in managerial positions than women and employees in other job positions (e.g., Hauge et al 2009 ;Lee and Brotheridge 2011 ). Thus, interventions to counteract workplace bullying should take into account the job position and gender of perpetrators and victims since these variables seem to play a pivotal role on how workplace bullying is perceived (e.g., Escartín et al 2011b, Hauge et al 2009Lee and Brotheridge 2011 ).…”
Section: Discussionsupporting
confidence: 91%
“…It is interesting to notice that in our study men and managers reported better mental health that women and employees in lower job positions. This finding is congruent with previous literature that has shown that: (a) women reported more negative health effects, such as post-traumatic symptoms, as a result of exposure to bullying behaviors (e.g., Rodríguez-Muñoz et al 2010 ); perpetrators of bullying are likely to be men and employees in managerial positions than women and employees in other job positions (e.g., Hauge et al 2009 ;Lee and Brotheridge 2011 ). Thus, interventions to counteract workplace bullying should take into account the job position and gender of perpetrators and victims since these variables seem to play a pivotal role on how workplace bullying is perceived (e.g., Escartín et al 2011b, Hauge et al 2009Lee and Brotheridge 2011 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, it has an insignificant correlation value that indicates that leadership is not the influencing factor to this behavior. As mentioned by Kantur (2010), and Lee and Brotheridge (2011), there are various factors that can influence the employees behavioral outcome, which include various contextual factors, situational factors, and personal factors. Within the organizational environment, these factors interact with each other and potentially influence deviant behavior.…”
Section: Relationship Between Leadership and Deviant Behaviormentioning
confidence: 99%
“…Cheung and Tang, 2010;Yeung et al, 2011, Lee andBrotheridge, 2011). There are two reasons for these incongruities.…”
Section: Introductionmentioning
confidence: 99%